Synthesis and Characterization of Mononuclear Copper(II) Complex with 5,5'-Dihydroxy-2,2'-[1,1'-(propane-1,3-diyldioxydinitrilo)dimethylidyne]diphenol - Yang, Yu-Hua; Meng, Jiao-Long; Li, Gang; Zhang, Li-Sha; Zhang, Xin-Ying; Wang, Zheng-Kun (Asian Journal of Chemistry, 2013)
Copper(II) complex [Cu(H2L)]·CH3CH2OH·0.5H2O has been synthesized by the reaction of copper(II) acetate monohydrate with 5,5'-dihydroxy-2,2'-[1,1'-(propane-1,3-diyldioxydinitrilo)dimethylidyne]diphenol in anhydrous ethanol medium and characterized by elemental analyses, molar conductance, IR spectra, UV-visible spectra and TG-DTA analyses.